Content, Forms And Means Of Preparing Future Economics For Professional Activity In A Digital Educational Environment - Salimov Esanjon Xusen o’g’li (Genius Journals, 2025)
In this article, we have highlighted the prerequisites for developing and testing a model for the formation of students' economic competence and identifying the pedagogical conditions necessary for organizing the educational process. We understand pedagogical conditions as a set of measures in the educational process that can ensure the successful and effective implementation of the model we have developed and contribute to the transition to a high level of formation of students' economic competence.
Keywords: modular; computer; stimulating students' reflective perspective